Adenosquamous carcinoma of the pancreas with clear cell and rhabdoid components. A case report. - Jamali, M; Serra, S; Chetty, R (2007)
CONTEXT: In as much as no such variant of this pancreatic tumour has been previously reported in the literature, we report an unusual case of an adenosquamous carcinoma of the pancreas characterized by clear cells and rhabdoid cells. CASE REPORT: A 75-year-old man presented with upper abdominal distention, dyspepsia, jaundice, and significant weight loss over a period of 3 months. Imaging of the abdomen showed a solid mass with cystic components in the region of the uncinate process of the pancreas. Endoscopic retrograde pancreatography showed mild to moderate dilatation of the intrapancreatic biliary tract and of the pancreatic duct, and a biliary stent was placed. The patient subsequently underwent a Whipple's procedure with curative intent. Histological evaluation of the pancreatic mass revealed an adenosquamous carcinoma displaying both clear cell and rhabdoid components. CONCLUSIONS: Assessing the predominant histology of pancreatic adenosquamous carcinoma variants such as those characterized by clear cells and rhabdoid cells may help select and improve upon therapies in this aggressive lesion.